Peran guru pendidikan agama islam dalam mencegah kasus bullying siswa di SMK Muhammadiyah 3 Wates Kulon Progo Yogyakarta - Windy Aprilia; Sutarman (At Turots: Jurnal Pendidikan Islam, 2023)
The background of the problem in this research is that there is a violent behavior at SMK Muhammadiyah 3 Wates which is committed by students to other students, the violence is bullying. This violence occurred due to factors both from within and from outside. To form good morals it takes effort from the teacher to prevent it. The aims of this research are (1) to find out the forms of bullying at SMK Muhammadiyah 3 Wates; (2) find out what factors cause students to bully at SMK Muhammadiyah 3 Wates; (3) knowing the role of PAI teachers in preventing bullying of students at SMK Muhammadiyah 3 Wates. This study uses a qualitative method with a descriptive approach. The research subjects consisted of 8 informants consisting of school principals, student vice presidents, 4 Islamic Religious Education teachers, and 2 students. The author uses data collection techniques through observation, interviews and documentation in order to obtain more valid data. After all the data is available, then a data analysis is carried out by reducing data, presenting data, and drawing conclusions. The results of this study indicate that there are two types of bullying that occur, namely verbal and physical bullying. Bullying violence is caused by several factors, namely (1) because students are looking for attention; (2) broken home children; (3) student morals are indeed not good (4) social media. So the role of the Islamic Religious Education teacher here is (1) educate; (2) provide examples; (3) guiding; (4) motivating students to behave well. This research is expected to be one of the ways or solutions in improving the quality of students, especially in fostering good morals for students so that they do not fall into acts of bullying against other students.